(untitled) (Global Journal of Management and Business Research, 2017)
The main objective of this study is to examine the impacts of implementing ISO9001:2008 practice towards employee’s job satisfaction in Dire tannery located in Addis Abeba Kolfe Keranyo sub city. The paper proposed main hypothesis and 4 sub-hypotheses and tests on the relationship between ISO9001:2008 practices and job satisfaction. The data for this study were collected using self-administered questioners from a total of 167 respondents in representative from seven departments of the tannery. Stratified sampling technique was used to draw samples out of the population. Out of this 167 questionnaires distributed 136 was collected back. The data was analyzed using descriptive statistics, correlation analysis and regressions. The result revealed that, customer focus; training and education, empowerment and team work and continues improvement are all positively associated with employee’s job satisfaction. It is also found that “empowerment and teamwork” and “continuous improvement” explains 46.5 percent of job satisfaction variance which is significant.